Oligonucleotides with Cationic Backbone and Their Hybridization with DNA: Interplay of Base Pairing and Electrostatic Attraction. Issue 7 (27th December 2017) - Schmidtgall, Boris; Kuepper, Arne; Meng, Melissa; Grossmann, Tom N.; Ducho, Christian
Abstract: Non‐natural oligonucleotides represent important (bio)chemical tools and potential therapeutic agents. Backbone modifications altering hybridization properties and biostability can provide useful analogues. Here, we employ an artificial nucleosyl amino acid (NAA) motif for the synthesis of oligonucleotides containing a backbone decorated with primary amines. An oligo‐T sequence of this cationic DNA analogue shows significantly increased affinity for complementary DNA. Notably, hybridization with DNA is still governed by Watson–Crick base pairing. However, single base pair mismatches are tolerated and some degree of sequence‐independent interactions between the cationic NAA backbone and fully mismatched DNA are observed. These findings demonstrate that a high density of positive charges directly connected to the oligonucleotide backbone can affect Watson–Crick base pairing. This provides a paradigm for the design of therapeutic oligonucleotides with altered backbone charge patterns. Abstract : Positivity : Nucleosyl amino acid (NAA) structures are employed for the synthesis of cationic oligonucleotides (see figure). Resultant oligo‐T analogues hybridize to native DNA with high affinity. Watson–Crick base pairing plays an essential role in this duplex formation, but unspecific electrostatic binding also contributes. This indicates that the number of positive charges in oligonucleotide analogues for biomedical applications needs to be limited.